Penerapan Model Problem Based Learning dengan Strategi Think, Talk, Write untuk Meningkatkan Keterampilan Menulis Teks Berita dalam Pembelajaran Bahasa Indonesia Siswa kelas VII B di SMPN 1 Jember - Ardianti Putri Lestari (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This Classroom Action Research (CAR) aims to improve the ability to write news texts through the application of the Problem Based Learning learning model with the Think, Talk, Write strategy in class VII B SMPN 1 Jember. Students have difficulty in writing news texts, especially in determining and developing ideas systematically and structured. This problem is caused by students' lack of understanding of the steps in writing news texts. The type of research conducted is classroom action research. The subjects of this study were all 33 students of class VII B SMPN 1 Jember. Data were obtained through observation, interviews, tests, and documentation. To analyze the data, qualitative and quantitative descriptive techniques were used. The results of the study showed that the application of the Problem Based Learning learning model with the Think, Talk, Write strategy succeeded in improving students' news text writing skills. This is evident from the increase in the average score for writing news texts in each cycle. In the pre-cycle, the average student score was 69%, with 12 students (36.6%) achieving completion and 21 students (63.4%) not completing. In cycle I, the average score increased to 73%, with 18 students (54.5%) completing and 15 students (45.5%) not completing. In cycle II, the average score reached 84.6%, with 33 students (100%) completing and reaching the KKM. Because 80% of students have achieved the KKM, this study was declared successful.
Entry oleh Arif 2026 Maret 27
Keywords: PBL; TTW; Writing skills; News text; SMPN 1 Jember